Gender Violence and the Representation of LGBTQIA+ Minorities in Videogames - Moreira, Giovane (2025)
This study aims to analyze the representation of minorities in video games and the gamer community. The chosen method of analysis was netnography. Data collection was conducted through semi-structured interviews and participant observation. Fieldwork began in November 2021, and the observation was concluded in February 2022. It was found that the representation of minorities in video games is still limited, with instances of hypersexualization of female bodies and a lack of LGBTQIA+ visibility. This absence is reflected in the gaming environment, perpetuating certain players’ behaviors when interacting with marginalized communities.